Formulation, characterization, and stability of food grade oil‐in‐water nanoemulsions of essential oils of Tasmannia lanceolata, Backhousia citriodora and Syzygium anisatum. Issue 5 (22nd July 2022) - Alderees, Fahad; Akter, Saleha; Mereddy, Ram; Sultanbawa, Yasmina
Abstract: Oil‐in‐water nanoemulsions were formulated using sunflower oil mixed with each of the essential oils of Tasmannia lanceolata (Tasmanian pepper leaf [TPL]), Backhousia citriodora (lemon myrtle [LM]) and Syzygium anisatum (anise myrtle [AM]) and stabilized with Tween 80 using ultrasonication. An oil‐surfactant ratio of 3:1 was found to produce the lowest emulsion droplet sizes of 96.6 nm for LM, 122.2 nm for AM and 131.8 nm for TPL. Increase in surfactant concentration above 10r resulted in larger droplet sizes, 165.8–2, 647.2 nm for LM (radius, r  = .82), 153.7–2, 573.5 nm for AM ( r  = .93) and 157.4–2, 621.6 nm for TPL ( r  = .83). Sonication for 3 min produced smaller droplet size; however, sonication for 9 min resulted in increase of droplet size by 1.48, 1.43 and 1.47 times for oils of LM ( r  = .82), AM ( r  = .93) and TPL ( r  = .83), respectively. A positive correlation was found between sonication amplitude (20–50%) and droplet size for nanoemulsions of LM ( r  = .93), AM ( r  = .98) and TPL ( r  = .95). TPL and LM nanoemulsions showed broad‐ spectrum antimicrobial activities against yeasts and bacteria. The minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) against weak‐acid resistant yeasts were between 0.001–0.003 and 0.002–0.007 mg/ml for nanoemulsion of TPL and between 0.003–0.014 mg/ml and 0.005–0.027 for nanoemulsion of LM, respectively. The stability and antimicrobial activity of TPL and LM essential oil nanoemulsions confirm their potential for application as food preservatives especially in beverage products that are commonly spoiled by weak‐acid resistant yeasts. Abstract : Nanoemulsions formulated from the of essential oils of Tasmannia lanceolata, Backhousia citriodora and Syzygium anisatum have strong antimicrobial activity against bacteria and fungi.